Prevalence of Blood Protozoa Disease on Cattle and Buffalo in Moyo Hilir Sub-District, Sumbawa District West Nusa Tenggara - Melani Anggraini; Hardany Primarizky; Mufasirin Mufasirin; Lucia Tri Suwanti; Poedji Hastutiek; Setiawan Koesdarto (Universitas Airlangga, 2019)
The aim of this research was to determine the type and prevalence of blood protozoa disease on cattle and buffalo in Moyo Hilir sub-district, Sumbawa District, Wes Nusa Tenggara. This research was taken on july until December 2018. This research used a non-experimental method through an observation study. The samples of this research were made in thin blood smear using 20% Giemsa’s stain and all samples were from 200 blood of cattle and buffalo in Moyo Hilir sub-district, Sumbawa District, West Nusa Tenggara. The results showed that the prevalence of blood protozoa disease was 11.5 Based on the type of blood protozoa, the highest prevalence was Anaplasma sp. (11%), followed by Theileria sp. (0.5%), while Babesia sp. And Trypanosoma sp. Were not found. Based on the livestock types, the prevalence in buffalo was higher (17%)than cttle (6%). Based on sex the prevalence in female was higher (12.6%) than male (10.11%). Based on age of livestock, the prevalance of livestock with age > 2 years old was higher (13.33%) than livestock with age ≤ 2 years old (10.4%) based on the location of the village, blood protozoa disease were only found in Olatrawa village (17.85%) and Serading village (17.82%), while in Kakiang and Moyo village were not found. The conclusion of this research indicate that prevalence of blood protozoa disease was 11.5% and only Anaplasma sp. And Theileria sp. Were found.